The Effect of Environmental, Social, and Governance and Human Capital on Company Performance (Case Study of Healthcare Sector Companies Listed on the Indonesia Stock Exchange for the Period 2021 - 2023) - Sabilla Meisya Putriani; Patria Prasetio Adi (Transpublika Publisher, 2025)
In an increasingly complex business environment, company success is influenced not only by financial factors but also by non-financial aspects such as Environmental, Social, and Governance (ESG) and human capital. ESG integrates environmental concerns such as better waste and emissions management, social responsibility towards employees and the community, and good corporate governance to ensure transparency and accountable decision-making, thereby increasing investor confidence, creating operational efficiency, and strengthening corporate sustainability. On the other hand, human capital focuses on managing human resources as intangible assets that have a central role in supporting the implementation of ESG values, through innovation, skills enhancement, and productivity. Companies with quality human capital tend to have better adaptability to industry changes, improve decision-making effectiveness, and strengthen innovation that contributes directly to improving company performance. This study examines the impact of ESG and human capital on company performance in the healthcare sector listed on the Indonesia Stock Exchange (IDX) for the period 2021–2023. Using a quantitative approach with multiple linear regression analysis, the research analyzes 11 purposively selected companies over three years, resulting in 33 data points. The findings indicate that ESG and human capital have a positive and significant partial effect on company performance. Simultaneously, ESG and human capital influence company performance, as evidenced by a high R Square value of 87.1%. This finding highlights the importance of integrating ESG principles and effective human capital management to support corporate sustainability.